Review of the book: Ethnocultural landscapes in the post-soviet space: problems and specifics of formation of Dagestan component (to the 90th anniversary of IHAE DSC RAS). Makhachkala: IHAE DSC RAS, 2014. - 238 p. - Tetuev, A I (History, Archeology and Ethnography of the Caucasus, 2015)
-